Fluid-like cathode enhances valuable biomass production from brewery wastewater in purple phototrophic bacteria - Manchon, Carlos; Asensio, Yeray; Muniesa-Merino, Fernando; Llorente, María; Pun, Álvaro; Esteve-Núñez, Abraham (Frontiers in Microbiology, 2023)
The climate crisis requires rethinking wastewater treatment to recover resources, such as nutrients and energy. In this scenario, purple phototrophic bacteria (PPB), the most versatile microorganisms on earth, are a promising alternative to transform the wastewater treatment plant concept into a biorefinery model by producing valuable protein-enriched biomass. PPB are capable of interacting with electrodes, exchanging electrons with electrically conductive materials. In this work we have explored for mobile-bed (either stirred or fluidized) cathodes to maximize biomass production. For this purpose, stirred-electrode reactors were operated with low-reduced (3.5 e-/C) and high-reduced (5.9 e-/C) wastewater under cathodic polarization (-0.4V and -0.8V vs. Ag/AgCl). We observed that cathodic polarization and IR irradiation can play a key role in microbial and phenotypic selection, promoting (at -0.4V) or minimizing (at -0.8V) the presence of PPB. Then, we further study how cathodic polarization modulates PPB biomass production providing a fluid-like electrode as part of a so-called photo microbial electrochemical fluidized-bed reactor (photoME-FBR). Our results revealed the impact of reduction status of carbon source in wastewater to select the PPB photoheterotrophic community and how electrodes drive microbial population shifts depending on the reduction status of such carbon source.